A novel robotic ureteral reconstruction technique for complex proximal strictures renal pelvis flap augmentation and buccal mucosal graft - Anh T. Nguyen; Jill C. Buckley (BMC Urology)
Abstract Introduction Complex proximal ureteral strictures can pose significant surgical challenges, including long or obliterated strictures, inability to perform primary anastomotic repairs, fixed renal pelvis, impaired vascular supply from prior surgeries, and poor healing of the proximal ureter. We describe a novel surgical technique for addressing these issues. Methods Our technique involves a combination of ureterolysis, renal pelvis flap creation, and buccal mucosal grafting. The procedure commences with exposure of the renal pelvis, creation of a U-shaped renal pelvis flap as the posterior plate and a buccal mucosa graft as the anterior plate. The omentum is then secured to provide a vascular bed for the graft. Results A total of 4 patients were included, with a mean age of 49 years. The median operating time was 4.08 h. The median post-operative length of stay was 1.5 days. At initial mean radiographic follow-up period of 3.2 months the success rate of the reconstruction was 100% with all patients demonstrating complete resolution of symptoms and radiographic improvement. Long-term follow-up was on average 22.3 months with sustained stability/improvement in radiographic hydronephrosis and symptoms, with no evidence of stricture recurrence. There were no donor site complications. Conclusion This novel surgical technique, involving ureteroplasty with a renal pelvis flap augmentation and buccal mucosal graft (RPFA-BMG), proves effective for complex proximal ureteral reconstruction. It is particularly suitable for long proximal obliterated strictures that require a combination of tissue transfer techniques for successful ureteral reconstruction and achievement of physiologic drainage.